Antimicrobial peptide GL13K immobilized onto SLA-treated titanium by silanization: antibacterial effect against methicillin-resistant Staphylococcus aureus (MRSA). Issue 11 (2nd March 2022) - Li, Yusang; Chen, Ruiying; Wang, Fushi; Cai, Xinjie; Wang, Yining
Abstract : Herein, an antimicrobial peptide coating was fabricated on SLA-treated titanium surface. The coating has shown significant antibacterial effect against MRSA with no cytotoxicity against osteoblast. Abstract : Infection is the main reason for implant failure, and the incidence of drug-resistant bacterial infection has increased in recent years. Further, methicillin-resistant Staphylococcus aureus (MRSA)-related implant infection has become a serious worldwide threat. New strategies, other than antibiotics, to tackle drug-resistance, are of high clinical significance. Antimicrobial peptides show clear superiority over conventional antibiotics in inhibiting drug-resistant bacteria. In the present study, we combined the antimicrobial peptide, GL13K, with sandblasting and acid-etching (SLA)-treated titanium using a silane coupling agent. Field emission scanning electron microscopy images showed the morphology of the coating. Attenuated total reflectance Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy results confirmed loading of GL13K, and the hydrophilicity of the SLA-GL13K coating was evaluated by water contact angle analysis. The releasing study of samples showed that the coating has a sustained releasing profile. SLA-GL13K coating exhibited strong contact- and release-killing abilities against MRSA, E. coli, and S. aureus . Meanwhile, Cell Counting Kit 8 analysis and examination of cell morphology demonstrated that the SLA-GL13K coating had good cytocompatibility at antibacterial concentrations. Overall, all these results suggest that SLA-GL13K coating can be successfully fabricated using silanization, and is a promising candidate for controlling MRSA-induced implant-related infection.